2021
DOI: 10.3390/ijerph18168624
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Lifestyle and Academic Performance in Middle School Students from the Region of Aragón (Spain)

Abstract: A healthy lifestyle is important to the present and future development and health of school age people. This study aims to analyze the relationship between daily lifestyle habits and academic performance in a sample of adolescents from the autonomous community of Aragon (Spain). We performed a cross-sectional study to analyze the lifestyle habits and academic performance of a total of 1745 7th and 8th grade middle school students during the academic year 2018–2019; the participants were selected from a random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Also, as might be expected, unhealthy lifestyle habits have been linked to worse academic results ( Harlé & Desmurget, 2012 ; Rodericks et al, 2018 ; Navalon & Ruiz-Callado, 2017 ). In line with this, we expected students attending HPS to lead a healthier life and also to achieve better academic results than those attending a non-HPS ( Sánchez-Hernando et al, 2021a ). However, as opposed to previous studies ( Yuasa et al, 2015 ; Lee et al, 2019 ; Arthur et al, 2011 ; Passmore & Donovan, 2014 ), we found that students attending non-HPS consumed more vegetables and less sugary drinks, and exercised more frequently and for longer periods, both individually and as a group, than students attending HPS.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Also, as might be expected, unhealthy lifestyle habits have been linked to worse academic results ( Harlé & Desmurget, 2012 ; Rodericks et al, 2018 ; Navalon & Ruiz-Callado, 2017 ). In line with this, we expected students attending HPS to lead a healthier life and also to achieve better academic results than those attending a non-HPS ( Sánchez-Hernando et al, 2021a ). However, as opposed to previous studies ( Yuasa et al, 2015 ; Lee et al, 2019 ; Arthur et al, 2011 ; Passmore & Donovan, 2014 ), we found that students attending non-HPS consumed more vegetables and less sugary drinks, and exercised more frequently and for longer periods, both individually and as a group, than students attending HPS.…”
Section: Discussionmentioning
confidence: 87%
“…Regarding the students’ lifestyle habits, namely diet, sleep, physical exercise, use of screens and substance abuse, we observed that lifestyle habits do have an impact on academic performance ( Sánchez-Hernando et al, 2021a ). Some authors ( Kristjánsson, Sigfúsdóttir & Allegrante, 2010 ; Barchitta et al, 2019 ; Chacón-Cuberos et al, 2018 ; Burrows et al, 2017 ) have reported a positive association between healthy eating and academic performance, others ( Morón et al, 2018 ; Portoles & González, 2015 ) have found an association between sleep and academic achievement, and others, such as Kristjánsson, Sigfúsdóttir & Allegrante (2010) and Sánchez Pérez (2015) , confirmed that those students who exercised more, achieved better academic results.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations